2021
DOI: 10.1111/add.15324
|View full text |Cite
|
Sign up to set email alerts
|

Impact of policy changes on the provision of naloxone by pharmacies in Ontario, Canada: a population‐based time–series analysis

Abstract: Background and aims In June 2016, the Ontario, Canada government implemented the Ontario Naloxone Program for Pharmacies (ONPP), authorizing pharmacists to provide injectable naloxone kits at no charge to all Ontario residents. In March 2018, the program was amended to include intranasal naloxone and remove the requirement to present a government health card to the dispensing pharmacist. We examined whether these changes increased naloxone dispensing through the ONPP. Design Population‐based time–series analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In 2022, 85% of accidental overdose deaths in Canada included fentanyl [4]. Responses to the worsening overdose crisis include expanded distribution of naloxone [5], implementation of additional supervised consumption services and overdose prevention sites [6], and expanded use of and access to opioid agonist therapy (OAT), including the introduction of injectable OAT programs [6,7]. These responses have contributed to the prevention of some overdose-related deaths [8].…”
Section: Introductionmentioning
confidence: 99%
“…In 2022, 85% of accidental overdose deaths in Canada included fentanyl [4]. Responses to the worsening overdose crisis include expanded distribution of naloxone [5], implementation of additional supervised consumption services and overdose prevention sites [6], and expanded use of and access to opioid agonist therapy (OAT), including the introduction of injectable OAT programs [6,7]. These responses have contributed to the prevention of some overdose-related deaths [8].…”
Section: Introductionmentioning
confidence: 99%
“…1 This crisis is driven primarily by contamination of the unregulated drug supply with illicitly derived fentanyl and fentanyl analogues, which directly contributed to 87% of opioid-related deaths in Ontario in 2020. 2 In response, several interventions have been adapted or scaled up, including the distribution of naloxone to reverse opioid overdose, 3 supervised consumption services and overdose prevention sites, 4,5 opioid agonist therapy (OAT) and injectable OAT programs (iOAT). [6][7][8] Evidence suggests that the expansion of these harm-reduction interventions across…”
mentioning
confidence: 99%
“…In Canada and the United States, an increasing number of studies have shown that naloxone access laws (e.g., laws that permit naloxone distribution without patient-specific prescriptions, laws that permit the medication to be dispensed in non-medical settings) have led to increased naloxone distribution (Antoniou et al, 2021;Smart, Pardo, & Davis, 2021).…”
Section: Discussionmentioning
confidence: 99%